Route Optimization for Motorcycle Riders Using A* Algorithm to Enhance Fuel Efficiency - Chan, Andi Supriadi; Daulay, Rizky Ananda Alam Syah; Lubis, Muhammad Farhan (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
This research focuses on the development of a route optimization application designed to help motorcycle users reduce fuel consumption. Leveraging the Google Maps API and the A* algorithm, the application identifies the most efficient routes by analyzing factors such as road distance, traffic conditions, and elevation. The system is tailored to benefit motorcyclists, both those using carburetors and fuel injection systems, who frequently face fuel inefficiency due to improper route selection. By integrating real-time data from Google Maps, the application provides users with optimal route recommendations that not only minimize fuel usage but also reduce travel time. The A* algorithm was selected due to its high efficiency in determining the shortest paths by considering multiple variables simultaneously. Through simulations and testing, the system demonstrates significant potential to improve navigation efficiency, particularly for long-distance commuters. This solution is expected to contribute to cost savings and more environmentally friendly transportation choices.